Managing the olympic heritage as the most important direction of the tourist complex development of the Krasnodar territory - M. K. Kovaleva (Новые технологии)
The article deals with the issues of development, preservation and effective functioning of the Olympic heritage sites located on the territory of Sochi. It is shown that the competent alignment of the system of eventual events that use the material and non-material potential of this heritage is one of the most important tasks of its management. At the same time, the realization of the Olympic heritage potential and definition of the most promising areas of tourism in the Krasnodar Territory are viewed both in internal and external aspects.